Effect of Policy Network Manager's Role on Public Policy Process Outcomes in the Road Transport Sector in Nairobi City County, Kenya - Ombagi, Cornelius; Minja, David; Muna, Wilson (American Journal of Public Policy and Administration, 2023)
Purpose: The policy network managers play an important role of providing a vital link between government, the public, and the policy makers ensuring that policies are effectively communicated and implemented, and that public opinion is accurately reflected in the decision-making process. They also ensure coordination of the activities of stakeholders, supporting policy development, and helping to ensure that policy decisions are made in the best interests of the public. Therefore, to ensure that the public policy process outcomes are well achieved, the policy network manager's roles must be well defined. Due to the recurring challenges in the policy making process in the transport sector in Nairobi City County Kenya, this study sought to explore the effect of policy network manager's role on public policy process outcomes in the Road Transport Sector in Nairobi City County, Kenya. Methodology: The study adopted a descriptive research design. The target population of the study was 470 policy actors in the road transport sector within Nairobi City County out of which 407 were purposefully sampled to respond to the questionnaire and 45 were sampled to participate in focused group discussions as well as key informant interviews. The sampling approach adopted was a purposeful sampling procedure. A mixed methodology was adopted whereby both quantitative and qualitative data was collected through structured questionnaires, Key Informant Interviews and focused group discussions. The quantitative data was analyzed through descriptive statistics that is mean, frequencies and percentages as well as regression analysis. On the other hand, qualitative data was analysed through thematic analysis and reported in a narrative format. Findings: The findings indicated that an improvement in policy network managers "˜roles would result to a significant improvement in the policy process outcomes. Recommendations: This study recommends the policy actors in the public policy making process in the transport sector in Nairobi City County, Kenya to increase visibility of the manager's roles. The study also recommends for a need to build trust and relationships as well as embrace and support evidence-based information. Another recommendation is the need for the policy network manager to facilitate collaboration between stakeholders and facilitate the exchange of information and ideas.